Systematic Literature Review: Tren Gamifikasi dalam Mobile-Assisted Language Learning - Muhammad Rakha Naufal; Arista Pratama; Anita Wulansari (MDP Student Conference, 2026)
This study investigates the impact of gamification trends in Mobile-Assisted Language Learning (MALL) through a Systematic Literature Review (SLR). The study aims to identify dominant gamification elements and examine their contribution to language learning effectiveness. The review was conducted using the PRISMA protocol, supported by clear inclusion–exclusion criteria and quality assessment to ensure methodological rigor. Fifteen journal articles published between 2022 and 2026 were analyzed. The findings indicate that points/XP, feedback, and leaderboards are the most frequently applied gamification elements in MALL. Overall, gamification demonstrates a positive impact on language learning by enhancing learners’ motivation, engagement, learning consistency, and vocabulary retention. These results confirm that gamification serves as an effective pedagogical strategy in supporting mobile-based language learning when implemented with appropriate instructional design.